Nutritional supplements improve cardiovascular risk factors in overweight and obese patients: A Bayesian network meta-analysis - Yu, Zengli; Zhao, Danyang; Liu, Xinxin (Frontiers in Nutrition, 2023)
Background: Overweight and obesity are considered as one of the major risk factors for cardiovascular diseases (CVD). At present, many studies have proved that multiple nutritional supplements play an active role in metabolic diseases. However, the comparative efficacy of different nutritional supplements in improving indicators of cardiometabolic risk in obese and overweight patients is uncertain. Methods: Cochrane Library, PubMed, Embase, and Web of Science were searched for the period from January 1990 to March 2022. A random-effect model was built in the Bayesian network meta-analysis. The surface under the cumulative ranking analysis (SUCRA) and clustering rank analysis was performed for ranking the effects. Results: The study included 65 RCTs with 4241 patients. In terms of glucose control, probiotic was more conductive to improve FBG (MD: -0.90; 95%CrI: -1.41 to -0.38), FINS (MD: -2.05; 95%CrI: -4.27 to -0.02), HOMA-IR (MD: -2.59; 95%CI -3.42 to -1.76). Probiotic (MD: -11.15, 95%CrI -22.16 to -1.26), omega-3 (MD: -9.45; 95%CrI: -20.69 to -0.93), VD (MD: -17.86; 95%CrI: -35.53 to -0.27), and probiotic +omega-3 (MD: 5.24; 95%CrI: 0.78 to 9.63) were beneficial to the improvement of TGs, TC and HDL-C, respectively. The SUCRA revealed that probiotic might be the best intervention to reduce FBG, FINS, HOMA-IR; Simultaneously, α-lipoic acid, VD, and probiotic+omega-3 might be the best intervention to improve TGs, TC, and HDL-C, respectively. Cluster-rank results revealed probiotic had the best comprehensive improvement effect on glucose metabolism, and probiotic+omega-3 may have a better comprehensive improvement effect on lipid metabolism (cluster-rank value for FBG and FINS: 3290.50 and for TGs and HDL-C: 2117.61). Conclusions: Nutritional supplementation is effective on CVD risk factors in overweight and obese patients. Probiotic supplementation might be the best intervention for blood glucose control; VD, probiotic+omega-3 have a better impact on improving lipid metabolism. Further studies are required to verify the current findings.